2009
DOI: 10.1007/s10735-010-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression of laminin and smooth muscle actin in the testis and epididymis of poultry and rabbit

Abstract: The present investigation was conducted to demonstrate laminin and alpha smooth muscle actin (alphaSMA) in the testis and epididymis of adult chickens, Sudani ducks, pigeons, and rabbits. This study may represent the first indication for the presence of laminin in the male reproductive organs of birds and rabbits and might therefore serve as a milestone for further reports. In the testis of chicken, Sudani duck, pigeon, and rabbit, the laminin was localized in the basal lamina of the seminiferous tubules and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…This agrees with the findings reported in the epididymal duct from different mammalian [2, 7, 9, 44] and avian species [44]. α-SMA is very significant to study SMCs differentiation under normal and pathological conditions [27].…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with the findings reported in the epididymal duct from different mammalian [2, 7, 9, 44] and avian species [44]. α-SMA is very significant to study SMCs differentiation under normal and pathological conditions [27].…”
Section: Discussionsupporting
confidence: 90%
“…It has previously been shown that cross talk between different cell types is essential for normal epididymal functions, and for example the communication between clear cells and other epithelial cell types is required to maintain luminal pH [33]. Interestingly, there are species-specific differences in thickness and distribution of the epididymal smooth muscle cell layer [34][36]. Further investigations regarding smooth muscle cell differentiation could thus benefit from comparative studies of different species.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, myoid cells in the tunica albuginea were characterized by the presence of desmin and SMA. These cytoskeletal proteins have also been immunolocalized in the tunica albuginea of other avian species including the domestic fowl (Maretta and Marettova, ; Abd‐Elmaksoud, ), ratites (Ozegbe et al., ) and masked weaver (Ozegbe et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical and electron microscopy techniques have been used to demonstrate smooth muscle or myoid cells in the testicular capsule of mammalian (Hargrove et al., ; Chacon‐Arellano and Woolley, ; Santamaria et al., ; Banks et al., ) and avian species (Aire and Ozegbe, ; Ozegbe et al., , ). Myoid cells in the testicular capsules of birds have been shown to contain various cytoskeletal proteins including smooth muscle actin (SMA) (Maretta and Marettova, ; Abd‐Elmaksoud, ; Ozegbe et al., ), desmin (Maretta and Marettova, ; Ozegbe et al., ) and vimentin (Aire and Ozegbe, ; Ozegbe et al., ).…”
Section: Introductionmentioning
confidence: 99%